High-radiance phosphor-converted light sources for fluorescence analysis - Jan Müller; Jan Müller; Ingo B. Ramsteiner; Reinhold Fieß; Cornelius Neumann (Advanced Optical Technologies)
Introduction/PurposeLaser-excited remote phosphor (LERP) light sources have gained significant importance in lighting and display applications due to their unique brightness and color-rendering qualities. In addition to their well-known advantages in these areas, we found that they also offer largely unexplored potential for sensor applications, such as quantitative fluorescence analysis. This potential is especially relevant when sophisticated optics operating under space and cost constraints require low-etendue sources with highly stable spectral properties. In this paper, we present an example of such an application. The purpose of our research is to assess currently available phosphor materials and design a light source to our particular reference application.MethodsFor this purpose, a characterization setup was developed that compares different phosphors excited by small laser spots, with diameters between 100 μm and 280 μm, in terms of emitted spectral radiance, incident laser power, and irradiance.ResultsThe investigation identified two suitable phosphors, including a phosphor that addresses the gap in the blue and green wavelength ranges. Furthermore, the importance of small laser spots was demonstrated, which allows reducing the laser power to simplify light source design and reduce costs.Discussion/ConclusionThis research proposes a functional set of phosphors for the abovementioned application and, at the same time, presents the current limitations of LERP light sources. We remain confident in the described application field for LERP sources and hope that the needs elaborated in this work will inspire further research and development of novel phosphor materials.